Comparative genomic analysis of Campylobacter hepaticus genomes associated with spotty liver disease, Georgia, United States - Ienes-Lima, Julia; Becerra, Roel; Logue, Catherine M. (Frontiers in Microbiology, 2023)
Campylobacter hepaticus has re-emerged as a cause of disease in egg laying birds worldwide, resulting in morbidity, mortality, and significant losses in eggs for the breeding and table egg laying industries. Although birds may appear asymptomatic, the disease is characterized by spots on the liver of birds and histopathological analysis reveals multifocal fibrogranulocytic necrotizing hepatitis microscopically. The re-emergence of C. hepaticus may be linked with housing practices as the disease appears more prevalent in pasture raised birds with outside exposure. Here we describe, the whole genome sequences and comparative analysis of four C. hepaticus genomes associated with an outbreak on pasture raised breeders from a farm in Georgia, USA. All four genomes were relatively similar in size and virulence genes harbored. Using these genomes, comparison with current C. hepaticus genomes available in NCBI and other databases and members of the Campylobacter species was carried out. Using current tools available, virulence gene factor content was compared, and it was found that different tools lead to different numbers of factors identified. The four genomes from this study were relatively similar to C. hepaticus HV10 the type strain from Australia but differed from the other sequenced US strains from Iowa and Florida. C. hepaticus was found to have an overall lower gene content for genes associated with virulence and iron acquisition compared to other Campylobacter genomes and appears to cluster differently than UK genomes on phylogenetic analysis, suggesting the emergence of two lineages of C. hepaticus. This analysis provides valuable insight into the emerging pathogen C. hepaticus, its virulence factors and traits associated with disease in poultry production in the US, potentially providing insight into targets for its control and treatment for laying birds. Our analysis also confirms genes associated with iron acquisition are limited and the presence of the multidrug efflux pump CmeABC in C. hepaticus which may promote survival and persistence in the host niche - the chicken liver/bile. One unique aspect of this study was the finding of a close genetic relationship between C. hepaticus and Campylobacter. fetus species and evidence of genome reduction in relation to host niche specificity.